Urolithins: The Colon Microbiota Metabolites as Endocrine Modulators: Prospects and Perspectives - Vini, Ravindran; Azeez, Juberiya M.; Remadevi, Viji; Susmi, T. R.; Ayswarya, R. S.; Sujatha, Anjana Sasikumar; Muraleedharan, Parvathy; Lathika, Lakshmi Mohan; Sreeharshan, Sreeja (Frontiers in Nutrition, 2022)
Selective estrogen receptor modulators (SERMs) have been used in hormone related disorders and their role in clinical medicine is evolving. Tamoxifen and raloxifen are the most commonly used synthetic SERMs and their long term use are known to create side effects. Hence, efforts have been directed to identify molecules which could retain the beneficial effects of estrogen at the same time produce minimal side effects. Urolithins, the products of colon microbiota from ellagitannin rich foodstuff, have immense health benefits and have been demonstrated to bind to estrogen receptors. This class of compounds holds promise as therapeutic and nutritional supplement in cardiovascular disorders, osteoporosis, muscle health, neurological disorders and cancers of breast, endometrium and prostate or in essence, most of the hormone/ endocrine dependent diseases. One of our findings from the past decade of research on SERMs and estrogen modulators, showed that pomegranate, one of the indirect, but major, sources of urolithins can act as SERM.The prospect of urolithins to act as agonist, antagonist or SERM will depend on its structure, the estrogen receptor conformational change, ,availability and abundance of co-activators / co-repressors, in the target tissues and also the presence of other estrogen receptor ligands,. Nonetheless,, SERMs need to be carefully studied for its benefits and adverse effects considering the pleotropic action of estrogen receptors and its numerous roles in physiological systems,. In this review, we unveil the possibility of urolithins as potent SERMs which, we are currently investigating, in hormone dependent tissues.